(untitled) (Journal of the Bangladesh Agricultural University, 2010)
A nucleus-breeding flock of selected Black Bengal goat was established in the Bangladesh Livestock Research Institute (BLRI) with the objective of conservation and improvement of the breed. A total of 120 does of different generations (70=foundation stock, 45=First generation and 5=Second generation) and 20 bucks (15=Foundation stock and 5=First generation) were used to study the genetic parameters of Black Bengal goat on productive and reproductive traits. Animals were bred naturally. Goats were reared under intensive and semi-intensive management to compare performance. Birth weights of kids were 1.49±0.13 and 1.28±0.11 kg, respectively for intensive and semiintensive rearing system. Number of services required for each successful conception was 1.16±0.019 with an average gestation length of 143.33±0.68 days. Litter size increased (P<0.001) linearly with parity. Average litter size of Black Bengal goat was 1.94±0.06. Rearing system, season, parity, generation and generation × parity interaction did not affect (P>0.05) the post partum estrous interval. Young females attained puberty at an age and weight of 186.02±10.52 days and 9.4±0.52 kg, respectively. In case of intensive rearing system it took 139 days to show 1st heat compared to 198 days in semi-intensive rearing system. Intensive system reduced the age at 1st kidding to 284±31.2 days from 370±25.5 days in semi-intensive system. The effects of parity, generation, and generation × parity interaction on kidding interval were not significant (P>0.05). The average daily milk yield and lactation length was 1.088 kg (750g suckled milk + 338g from hand milking) and 68.07±2.83 days respectively. The effect of parity and generation on doe weight after kidding was significant (P<0.01) but the effect of generation × parity interaction was not significant (P>0.05). Heritability estimates from sire and dam component for birth weight, weight at 3, 6, 9, 12 months of age and litter size were 0.92, 0.48, 0.34, 0.45, 0.88 and 0.17, respectively. Heritability estimates only from sire component for birth weight, weight at 3, 6, 9, 12 months of age and litter size were 0.05, 0.28, 0.77, 0.29, 0.18 and 0.15, respectively. Repeatability estimates for birth weight, litter size, kidding interval and daily milk yield were 0.47, 0.15, 0.02 and 0.49, respectively. Keywords: Black Bengal goat; Performance traits; Heritability; Repeatability DOI: 10.3329/jbau.v8i1.6401 J. Bangladesh Agril. Univ. 8(1): 67-78, 2010